Fostering Inclusive Growth: Application of Islamic Economy and Social Market Economy Models in Tourism Villages - Asep Kurniawan; Windia Windia (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2026)
Purpose: This paper develops an integrative conceptual framework, the Islamic-Social Market Economy for Tourism (ISMET) Model, that synthesizes core principles of Islamic Economy (IE) and Social Market Economy (SME) to foster inclusive growth in tourism villages in developing, Muslim-majority countries. Design/methodology/approach: The study adopts a qualitative, conceptual-comparative research design from theoretical literature on Islamic economics, ordoliberal social market economy theory, inclusive growth, and community-based tourism, followed by abductive theory-building. Findings: The comparative analysis identifies four convergent pillars linking IE and SME: economic inclusion through ethical market participation, social inclusion via redistributive instruments, governance inclusion through deliberative decision-making, and environmental inclusion under a stewardship ethic. These pillars are operationalized into concrete mechanisms, musharakah-cooperative enterprises, waqf-funded social infrastructure, subsidiarity-shura community councils, and khalifah-grounded carrying-capacity regulation, mapped against measurable inclusive-growth indicators. Practical implications: The ISMET Model offers policymakers, village cooperatives, and development agencies in Indonesia, Malaysia, Morocco, and Jordan an implementable governance architecture that channels tourism revenue toward local ownership, social welfare, participatory governance, and ecological sustainability. Originality/value: This is the first study to systematically integrate Islamic Economy and Social Market Economy theory into a unified governance framework for tourism village development, extending Sen's capability approach and directly engaging Kuran's critique of Islamic economic institutions.